Dietary knowledge among adults with type 2 diabetes - Kingdom of Saudi Arabia - Sami, Waqas; Alabdulwahhab, Khalid M.; Ab Hamid, Mohd Rashid; Alasbali, Tariq A.; Al Alwadani, Fahd; Ahmad, Mohammad Shakil (MDPI AG, 2020)
Dietary management is considered as a major step in assessing a patient’s knowledge related to nutritional aspects, treatment, and complications of diabetes. Diabetes patients frequently face difficulty in identifying the recommended diet, including its quality and quantity. In the Kingdom of Saudi Arabia (KSA), sedentary lifestyle, along with food choices and portion sizes, have increased considerably and this has resulted in the soaring risk of diabetes. In addition, there is paucity of literature focusing on the Dietary Knowledge (DK) of type 2 diabetics in KSA. The study aimed to assess and evaluate the DK of type 2 diabetics. An analytical cross-sectional study was conducted among 350 type 2 diabetics using a valid and reliable self-prepared questionnaire comprising of 21 questions. Results showed that type 2 diabetics had an overall poor DK (28.57%). Sub-group analysis further revealed that diabetes patients had poor knowledge related to the consumption of carbohydrates and food choices, whereas they had good knowledge related to lipids and fats, proteins and food types. The role of diet in controlling of diabetes is considered imperative, but still, diabetes patients are unaware how they should approach this issue. The patient empowerment approach can be used to counsel patients with a poor DK. Primary care physicians and dietitians should work together and carry out individualized, tailored and patient-centered dietary education sessions.